An introduction to quantum optics and quantum fluctuations - Milonni, Peter W. (Oxford graduate texts., 2019)
This is an introduction to the quantum theory of light and its broad implications and applications. The book covers material with direct relevance to current basic and applied research, such as quantum fluctuations and their role in laser physics and the theory of forces between macroscopic bodies. Includes many exercises and historical sidelights.